Comparative analysis of the approach to first language oracy of Polish and Portuguese early education teachers - Łockiewicz, Marta; Sousa, Otília; Fuertes, Marina; Piechowska, Martyna; Costa-Pereira, Teresa (Calidoscópio, 2023)
Oracy, crucial for individuals to communicate, think, and learn, can be developed through schooling. Our study aimed to compare Polish and Portuguese teachers’ perceptions of oracy. Based on a literature review, a self-report survey was developed for the study. It comprised questions about: 1. the demographic information, 2. the practices in the classrooms, 3. teachers’ views and attitudes about oracy. 253 (62.00%) Portuguese and 157 (38.00%) Polish elementary school teachers participated. Our main results indicate that Polish and Portuguese teachers declared that they valued oracy, and devoted time during their lessons to promote and support its development in their students. However, the Portuguese teachers, as compared with the Polish teachers, focused more on discussions and debates among students, and allowed them more autonomy in their classrooms. They also appreciated more the importance of oracy for human development, including reasoning and literacy learning. Keywords: Oracy; Mandatory Education; Polish; Portuguese; Teachers.